2022
DOI: 10.3389/fcvm.2022.874436
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma Transcriptome Implicates Dysregulated S100A12 Expression: A Strong, Early-Stage Prognostic Factor in ST-Segment Elevated Myocardial Infarction: Bioinformatics Analysis and Experimental Verification

Abstract: The ability of blood transcriptome analysis to identify dysregulated pathways and outcome-related genes following myocardial infarction remains unknown. Two gene expression datasets (GSE60993 and GSE61144) were downloaded from Gene Expression Omnibus (GEO) Datasets to identify altered plasma transcriptomes in patients with ST-segment elevated myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention. GEO2R, Gene Ontology/Kyoto Encyclopedia of Genes and Genomes annotations, protein–pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…The diagnostic accuracy of CAP1 in AMI was similar to that of heart-type fatty acid binding protein (H-FABP) and S100 calcium binding protein A12 (S100A12), but was lower than that of Cardiac myosin-binding protein C (cMyBP-C). [28][29][30] Moreover, CAP1 combined with cTnI has superior diagnostic value than CAP1 and cTnI alone, indicating the combination of CAP1 and cTnI as biomarkers in clinical practice is feasible and effective. In addition, the expression of CAP1 in participants of patients with first-time AMI was positively interrelated with ox-LDL level, and CAP1 expression was increased in ox-LDL induced HUVEC in a doseand time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy of CAP1 in AMI was similar to that of heart-type fatty acid binding protein (H-FABP) and S100 calcium binding protein A12 (S100A12), but was lower than that of Cardiac myosin-binding protein C (cMyBP-C). [28][29][30] Moreover, CAP1 combined with cTnI has superior diagnostic value than CAP1 and cTnI alone, indicating the combination of CAP1 and cTnI as biomarkers in clinical practice is feasible and effective. In addition, the expression of CAP1 in participants of patients with first-time AMI was positively interrelated with ox-LDL level, and CAP1 expression was increased in ox-LDL induced HUVEC in a doseand time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the AUC value of S100A12 was as high as 0.896, indicating its great potential as a diagnostic marker for AMI. Interestingly, several studies have also suggested that S100A12 could be a diagnostic biomarker for early AMI (40,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…These datasets—namely GSE29111, GSE60993, GSE61144, GSE34198, GSE49925, and GSE34571—represented the most prevalent sample types. However, due to specific limitations [ 11 ], we excluded datasets GSE29111, GSE34198, and GSE34571. To facilitate our analysis, we selected three datasets (GSE49925 [ 12 ], GSE60993 [ 13 ], and GSE61144 [ 13 ]) for further investigation.…”
Section: Methodsmentioning
confidence: 99%
“…Our prior research has illuminated the prognostic significance of specific IRGs, including CD8A , IL2RB , and S100A12 , within the context of STEMI [ 11 ]. These findings underscore the potential of integrating clinical parameters with IRG profiles to construct a robust predictive model for patient outcomes.…”
Section: Introductionmentioning
confidence: 99%